2021
DOI: 10.1002/anie.202014929
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity and Selectivity in Ruthenium Sulfur‐Chelated Diiodo Catalysts

Abstract: A trifluoromethyl sulfur‐chelated ruthenium benzylidene, Ru‐S‐CF3‐I, was synthesized and characterized. This latent precatalyst provides a distinct activity and selectivity profiles for olefin metathesis reactions depending on the substrate. For example, 1,3‐divinyl‐hexahydropentalene derivatives were efficiently obtained by ring‐opening metathesis (ROM) of dicyclopentadiene (DCPD). Ru‐S‐CF3‐I also presented a much more effective photoisomerization process from the inactive cis‐diiodo to the active trans‐diiod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 64 publications
1
25
0
Order By: Relevance
“…This strategy was previously implemented by Hoveyda et al via the substitution of chlorides by a catechothiolate ligand (see Scheme c), which resulted in a highly Z -selective catalyst and high yields for ROMP and ROCM . It is observed that this approach focused on stereoselectivity differs from other sulfur chelates previously reported, in which the ether R 2 O→Ru in HG catalysts is replaced by a thioether R 2 S→Ru, resulting in enhancements in the catalytic activity. It should be clarified, however, that we aimed at the formation of an active species that resembles the structure depicted in Scheme b. In this regard, several authors have previously reported predictive catalysis based on DFT calculations verified by experimental evidence. …”
Section: Introductionmentioning
confidence: 98%
“…This strategy was previously implemented by Hoveyda et al via the substitution of chlorides by a catechothiolate ligand (see Scheme c), which resulted in a highly Z -selective catalyst and high yields for ROMP and ROCM . It is observed that this approach focused on stereoselectivity differs from other sulfur chelates previously reported, in which the ether R 2 O→Ru in HG catalysts is replaced by a thioether R 2 S→Ru, resulting in enhancements in the catalytic activity. It should be clarified, however, that we aimed at the formation of an active species that resembles the structure depicted in Scheme b. In this regard, several authors have previously reported predictive catalysis based on DFT calculations verified by experimental evidence. …”
Section: Introductionmentioning
confidence: 98%
“… 17 20 Generally, ROMP offers access to single-structure, functional oligomers or polymers. 8 , 18 , 19 , 21 − 25 In that regards, controlling the stereoselectivity in ROMP is an ultimate driving force in catalyst design because the tacticity of a polymer is intricately linked to its properties. 23 In the case of norborn-2-ene (NBE), four different regular polymers can be formed (see Scheme 1 (left)); these are cis -syndiotactic ( cis -st), cis -isotactic ( cis -it), trans -syndiotactic ( trans -st), and trans -isotactic ( trans -it).…”
Section: Introductionmentioning
confidence: 99%
“…Olefin metathesis has become a key reaction in the formation of carbon–carbon bonds. The success can be attributed to the development of Mo- and W-based Schrock and Ru-based Grubbs initiators, which allow for such selective C–C coupling reactions under mild conditions and provide access to well-defined polymers with tunable properties. , Although more reactive, the fast deactivation of Mo-based catalysts in comparison to Ru-based catalysts prevented so far their broader use . By contrast, neutral, pentacoordinated and cationic, tetracoordinated Mo imido alkylidene N -heterocyclic carbene (NHC) complexes show improved stability not only toward oxygen, water, and protic substrates but also toward high temperatures without sacrificing reactivity and productivity. Indeed, these catalysts are characterized by an impressive functional group tolerance and allow for olefin metathesis reactions with hydroxyl-, carboxyl-, aldehyde-, ether-, and amine-containing substrates .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen atoms and solvent molecules were omitted for clarity. [21] Scheme 1. Reaction Scheme of 1,7-octadiene and DCPD derivatives in the presence of Ru-S-CF 3 -I.…”
mentioning
confidence: 99%